(untitled) (Journal of Parents and Teachers, 2014)
In the subject of Religion, the objective for students is to initiate them in the understanding of new knowledge in this field. However, to help the adolescent to become aware of their own inner, affective and emotional life. This is a dimension rarely contemplated in the curricular programmes of the subject of Religion. As a consequence, it is necessary to help young people become aware of their desires and dreams, as well as their feelings, abilities and limitations, etc. In addition, understanding and experience in the classroom must be combined. The latter requires greater preparation on the part of the teacher because he or she will have to promote and create contexts that allow the recognition of the primacy of a God who is related to our personal life.